Experimental analysis of sperm competition mechanisms in a wild bird population. - Michl, G; Török, J; Griffith, S; Sheldon, B (2002)
Recent work on wild birds has revealed the importance of sperm competition as a source of sexual selection, but behavioral and paternity studies have previously provided only indirect evidence for mechanisms of sperm competition in wild birds. In a field study of collared flycatchers Ficedula albicollis we used a previously uncharacterized method to determine the frequency and timing of extra-pair inseminations. By counting the number of sperm trapped on the perivitelline layer of eggs, we determined the timing of inseminations and estimated, on a day-to-day basis, the amount of sperm females stored. Our results showed that female collared flycatchers preferentially engaged in extra-pair copulations when mated to an unattractive male with a small white forehead patch. These copulations were timed for the middle part of their fertile period, at least 2 days after the last within-pair insemination. Although the mean number of extra-pair insemination events was only 1.33 per cuckolding female, the ratio between the number of sperm from extra-pair and pair inseminations was at least 5 to 1. Thus a single, well timed extra-pair insemination caused by female behavior could greatly bias fertilization probability in favor of an attractive extra-pair male. Our results suggest a possible behavioral mechanism for female control of sperm competition.